2018
DOI: 10.4103/0366-6999.230738
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking on Anal Abscess and Anal Fistula Diseases

Abstract: Background:Several studies have investigated the association between smoking and anal abscess and anal fistula (AA/F) diseases. However, the relationship between cigarette smoking and AA/F remains unclear. This study sought to assess the role of smoking in anorectal male patients in a Chinese population.Methods:In this retrospective study, a questionnaire, including smoking history, was completed over a 3-month period by male inpatients in the Proctology Department of China-Japan Friendship Hospital. “Cases” w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Also, a prospective study that assessed the long-term recurrence rate after anal surgery found that all fistulas occurred before 24 months [ 14 ]. In our study, smoking was not associated with greater risk of anal fistula, in contrast with published epidemiological data [ 10 , 11 , 15 ]. We cannot exclude a lack of statistical power since univariate analysis showed a significant association but multivariate analysis did not.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, a prospective study that assessed the long-term recurrence rate after anal surgery found that all fistulas occurred before 24 months [ 14 ]. In our study, smoking was not associated with greater risk of anal fistula, in contrast with published epidemiological data [ 10 , 11 , 15 ]. We cannot exclude a lack of statistical power since univariate analysis showed a significant association but multivariate analysis did not.…”
Section: Discussioncontrasting
confidence: 99%
“…Since the location of disease is a powerful indicator of behavior change, it could have suppressed the effect of smoking status due to a multicollinearity effect in the regression model. This might have led to a type II error regarding the influence of smoking on behavior change in the study by Aldhous et al [21] Also Zheng et al [22] reported that; smoking to be a potential risk factor for the development of anal abscess and anal fistula diseases in population without inflammatory bowel disease. In our study, location of disease was evenly distributed among patients with different smoking habits, and current smoking was found to be independently associated with intestinal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that smoking increases the risk of anal abscesses. Zheng et al 144 reported that smoking is associated with anal abscess and anal fistula disease (OR=12.331; 95% CI: 8.364-18.179). Devaraj et al 145 proved that the risk of anal abscess/anal fistula among military veterans with a smoking history within 1, 5 and 10 years was 2.15, 1.72, and 1.34 times that of non-smoking veterans, respectively.…”
Section: Smoking and Anal Abscessmentioning
confidence: 99%